Energetics of table tennis and table tennis-specific exercise testing - Moura Zagatto, A.; Vieira de Mello Leite, J.; Papoti, M.; Beneke, R. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To test the hypotheses that the metabolic profile of table tennis is dominantly aerobic, anaerobic energy is related to the accumulated duration and intensity of rallies, and activity and metabolic profile are interrelated with the individual fitness profile determined via table tennis-specific tests.